A covariant formulation of finite plasticity with plasticity-induced evolution of anisotropy: Modeling, algorithmics, simulation, and comparison to experiments. (1st March 2020) - Kaiser, Tobias; Lu, Jia; Menzel, Andreas; Papadopoulos, Panayiotis
Abstract: Motivated by experimental findings on sheet-metal forming, this article concerns the modeling of evolving anisotropies in finite plasticity. A covariant formulation of plasticity is employed in conjunction with evolution equations for the structural tensors that characterize the symmetry group of the yield function. A specific model is implemented into a finite element code to simulate tension and torsion tests. The results are then compared to experiments.